Correlation of NPM1 Type A Mutation Burden With Clinical Status and Outcomes in Acute Myeloid Leukemia Patients With Mutated NPM1 Type A - Jo, Su Yeon; Park, Sang Hyuk; Kim, In-Suk; Yi, Jongyoun; Kim, Hyung-Hoi; Chang, Chulhun L.; Lee, Eun Yup; Cho, Young-Uk; Jang, Seongsoo; Park, Chan-Jeoung; Chi, Hyun-Sook (Annals of laboratory medicine, 2016)
Nucleophosmin gene (NPM1) mutation may be a good molecular marker for assessing the clinical status and predicting the outcomes in AML patients. We evaluated the applicability of NPM1 type A mutation (NPM1-mutA) quantitation for this purpose. Twenty-seven AML patients with normal karyotype but bearing the mutated NPM1 were enrolled in the study, and real-time quantitative PCR of NPM1-mutA was performed on 93 bone marrow (BM) samples (27 samples at diagnosis and 56 at follow-up). The NPM1-mutA allele burdens (represented as the NPM1-mutA/Abelson gene (ABL) ratio) at diagnosis and at follow-up were compared. The median NPM1-mutA/ABL ratio was 1.3287 at diagnosis and 0.092 at 28 days after chemotherapy, corresponding to a median log10 reduction of 1.7061. Significant correlations were observed between BM blast counts and NPM1-mutA quantitation results measured at diagnosis (γ=0.5885, P=0.0012) and after chemotherapy (γ=0.5106, P=0.0065). Total 16 patients achieved morphologic complete remission at 28 days after chemotherapy, and 14 (87.5%) patients showed a >3 log10 reduction of the NPM1-mutA/ABL ratio. The NPM1-mutA allele was detected in each of five patients who had relapsed, giving a median increase of 0.91-fold of the NPM1-mutA/ABL ratio at relapse over that at diagnosis. The NPM1-mutA quantitation results corresponded to BM assessment results with high stability at relapse, and could predict patient outcomes. Quantitation of the NPM1-mutA burden at follow-up would be useful in the management of AML patients harboring this gene mutation.